STRESS AND STRUCTURE IN THE BENIOFF SEISMIC ZONE - Demin S.S.; Zharinov S.Y. (My University, 1988)
The Benioff seismic zones (BSZ) are important components of active continental margins (or island-arc systems) and are natural indicators of the stress in the geophysical medium and of the geodynamic conditions in the region. In this paper we present estimates of the stress in Benioff zones calculated from the deep-fault model. The analysis indicates that the type of stress-field distribution suggested by the deep fault model fits well the data on the structure of the real BSZ. In particular, the results computed from the model describe the two-layer structure of the Benioff seismic zone.